Implementasi Transparansi Pengelolaan Dana Desa dalam Program Bantuan Langsung Tunai (BLT) di Kota Lhokseumawe - Risna Dewi; Ahyal Fatha (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2026)
This study aims to analyze the implementation of transparency in the management of Village Funds within the Direct Cash Assistance (BLT) program in Lhokseumawe City. The study employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation involving village officials, community leaders, and beneficiaries. The findings indicate that transparency in BLT management has been implemented through village deliberation meetings, community participation in decision-making processes, the public announcement of beneficiary lists, and the transparent and accountable distribution of funds in accordance with Minister of Home Affairs Regulation Number 20 of 2018. These practices have contributed to improving public trust and ensuring greater accountability in the use of Village Funds. However, several obstacles remain, including budget limitations, changing socioeconomic conditions among residents, inaccuracies in beneficiary data, and the suboptimal complaint-handling mechanism. Therefore, strengthening data validation procedures, improving information disclosure, and enhancing the complaint management system are necessary to increase transparency, accountability, and the effectiveness of the Village Fund BLT program in Lhokseumawe City.